Office and SharePoint 2007 user's guide : integrating SharePoint with Excel, Outlook, Access, and Word - Antonovich, Michael P. (Expert's voice in Office., 2008)
Web sites. Collaboration. Document management. Paperless offices. We want it all in business today, but how do you achieve all of these goals? More importantly, if you work for one of the millions of small to medium sized businesses, how do you find the time and build the expertise necessary to reach these goals? Even the most powerful tool will not allow you to succeed unless you can get the majority of your staff to use it efficiently and effectively. You need a guide that demonstrates a platform small to medium sized businesses can use to reach these goals. Office and SharePoint 2007 User s.